‘Our Failure of Empathy’: Kevin Carter, Susan Sontag, and the Problems of Photography - Wai Kit Ow Yeong (Think Pieces, 2014)
To download this article, please click here. In a media-saturated age, can photographs still promote empathy? The commoditization and consequent banalization of photography has led not only to what has been condemned as the opportunistic exploitation of images by consumerist bourgeois society, but also the inhibition of empathy in discourse and practice. Exploring the role of photography in relation to empathy through an examination of the visual impact, psychological effects and emotional influence of photographic media, this paper builds on the work of Susan Sontag in On Photography (1977) and Regarding the Pain of Others (2003) to focus on the case of a Pulitzer Prize-winning image by the late South African photojournalist Kevin Carter. The haunting photograph, taken during the 1993 famine in Sudan, shows a starving Sudanese girl on her way to a feeding centre, shadowed by a vulture lurking behind her. Sontag’s observations are directly applicable to Carter’s case: the act of photographing may unconsciously encourage the prioritization of images above individuals, thus inhibiting empathy in the photographer. Overexposure to disaster images in the media also hampers viewers’ emotional identification with suffering photographic subjects, while the dominance of the Internet in the modern age may have in fact intensified photography’s anesthetizing effect. Viewer apathy further stems from the ways in which the photographic medium might influence one’s emotional responses by changing perceptions of people, and indeed, of time itself. Yet while photography may impose obstacles to empathy, the vital issue that Carter’s photograph demonstrates is not merely how photographs are taken but how they are interpreted, applied, and employed to prompt social action.